Preparation method and application of naphthalocyanine tin derivative oxidized tin / nitrogen-doped carbon composite negative electrode material

CN122907574APending Publication Date: 2026-10-13DEZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611189063.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

对于SnO2与碳材料的复合,现有制备方法多采用锡盐与外加碳源的后混合与复合、水热处理或喷雾热解等路线,工艺步骤繁复,且难以调控SnO2与碳相之间的界面接触质量及空间分布均匀性

Benefits of technology

[0031]本发明的有益效果为:本发明所述的萘酞菁锡衍生物氧化锡/氮掺杂碳复合负极材料的制备方法以萘酞菁锡单源前驱体为锡源、碳源和氮源,无需另行引入锡盐和外加碳源,工艺路线较为简洁。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907574A_ABST
    Figure CN122907574A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of lithium ion battery negative electrode materials, and particularly relates to a preparation method and application of a naphthalocyanine tin derivative tin oxide / nitrogen-doped carbon composite negative electrode material. The preparation method uses naphthalocyanine tin (SnNc) as a single-source precursor, and the naphthalocyanine tin single-source precursor is sequentially subjected to ball milling activation and acid swelling treatment before heat treatment, so as to adjust the particle dispersion state and molecular accumulation state of the naphthalocyanine tin single-source precursor, and obtain a modified naphthalocyanine tin precursor. Then, the modified naphthalocyanine tin precursor is subjected to inert atmosphere heat treatment, and air is introduced for oxidation during the cooling process, so as to obtain the naphthalocyanine tin derivative tin oxide / nitrogen-doped carbon composite negative electrode material. The obtained composite negative electrode material is synergistically optimized in terms of structural order, interface activity and transmission kinetics, exhibits a more open multi-level pore structure, significantly enhances the electrolyte wettability and active site accessibility, and simultaneously promotes the electron / ion synergistic transmission kinetics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of lithium-ion battery anode materials, specifically relating to a method for preparing a tin oxide / nitrogen-doped carbon composite anode material based on a tin phthalocyanine derivative. Background Technology

[0002] Lithium-ion batteries (LIBs) are widely used in portable electronic devices, electric vehicles, and energy storage systems due to their high energy density and long cycle life. As application scenarios demand higher energy density and faster charge / discharge performance, higher requirements are being placed on lithium-ion batteries, necessitating electrode materials that combine high energy density with excellent cycle stability. The theoretical specific capacity of traditional graphite anodes is only 372 mAh·g. -1 The current capacity of traditional graphite anodes is nearing its performance limit, indicating that the theoretical capacity of traditional graphite anodes is insufficient to meet the development requirements of high-performance lithium-ion batteries. Therefore, developing high-capacity anode materials has become a key direction for promoting the development of next-generation LIBs.

[0003] SnO2 has a high capacity of 1494 mAh·g -1 SnO2, with its theoretical lithium storage capacity, is a promising anode material for lithium-ion batteries. However, SnO2 undergoes complex conversion reactions (SnO2→Sn+Li2O) and alloying reactions (Sn+4,4Li) during charge and discharge. + +4.4e - Li 4.4 Sn), which causes SnO2 to undergo a dramatic volume change of about 300% during lithiation and delithiation, easily leading to the pulverization of active materials, the breakage of conductive networks, and repeated rupture and reconstruction of the solid electrolyte interphase (SEI) film, ultimately resulting in rapid capacity decay, insufficient rate performance, and limited cycle life.

[0004] Constructing a SnO2 / carbon composite structure is an effective way to improve the above-mentioned problems. The carbon component not only provides a continuous electron transport channel but also effectively buffers volumetric strain and maintains the overall integrity and stability of the electrode structure. For the composite of SnO2 and carbon materials, existing preparation methods often employ post-mixing and composite of tin salts and external carbon sources, hydrothermal treatment, or spray pyrolysis, which involve complex process steps and make it difficult to control the interfacial contact quality and spatial distribution uniformity between the SnO2 and carbon phases. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing a tin oxide / nitrogen-doped carbon composite anode material based on naphthalene phthalocyanine tin derivatives and its application.

[0006] This preparation method uses naphthalene phthalocyanine tin (SnNc) as a single-source precursor to provide tin, carbon, and nitrogen sources for the preparation of SnO2 / carbon composite materials. Before heat treatment, the naphthalene phthalocyanine tin single-source precursor is sequentially subjected to ball milling activation and acid swelling treatment to adjust its particle dispersion and molecular packing state, obtaining a modified naphthalene phthalocyanine tin precursor. Then, it undergoes inert atmosphere heat treatment, followed by air oxidation during cooling, to obtain a naphthalene phthalocyanine tin oxide / nitrogen-doped carbon composite anode material.

[0007] The tin-naphthalene phthalocyanine single-source precursor allows tin and carbon framework to originate from the same molecular precursor, thereby achieving component co-evolution at the atomic scale and providing a more controllable and simpler path for constructing SnO2 / carbon composite materials with uniform composition and tight interfaces.

[0008] However, during the research process, this invention discovered that although the tin mono-source precursor of naphthalene phthalocyanine can simultaneously provide tin, carbon and nitrogen sources, the strong π–π stacking interaction between naphthalene phthalocyanine molecules easily leads to precursor aggregation and dense stacking, affecting precursor dispersion and severely restricting its uniform decomposition and structural evolution in subsequent thermal conversion processes.

[0009] To this end, the present invention innovatively proposes to perform ball milling activation and acid expansion synergistic pretreatment on the naphthalene phthalocyanine tin single-source precursor before heat treatment. This synergistic pretreatment process can adjust the crystal structure of naphthalene phthalocyanine tin while maintaining the integrity of its conjugated macrocycle, thereby optimizing the physical state and microstructure of the precursor before thermal conversion, which is used to improve the particle dispersion and molecular packing state of the naphthalene phthalocyanine tin precursor.

[0010] After carbonization, the naphthalene-modified tin phthalocyanine precursor produces a nitrogen-doped porous carbon matrix composite material with a significantly expanded specific surface area and a richer mesoporous structure. Consequently, the resulting material exhibits better cycle performance and rate performance when used as a negative electrode material for lithium-ion batteries.

[0011] The specific technical solution is as follows: A method for preparing a tin oxide / nitrogen-doped carbon composite anode material derived from tin phthalocyanine, comprising the following steps: (1) Preparation of naphthalene phthalocyanine tin precursor; The naphthalene phthalocyanine tin precursor was prepared from 2,3-dicyanonaphthalene and anhydrous stannous chloride.

[0012] (2) Preparation of modified naphthalene phthalocyanine tin precursor: The naphthalene phthalocyanine tin precursor obtained in step (1) was subjected to ball milling activation and acid swelling treatment in sequence to obtain the modified naphthalene phthalocyanine tin precursor.

[0013] S1. Ball milling activation: A grinding medium was added to the naphthalene phthalocyanine tin precursor prepared in step (1), and ball milling activation was performed at 105-110℃.

[0014] S2, Acid Swelling Treatment: The ball-milled activated naphthalene tin phthalocyanine precursor was subjected to acid swelling treatment with sulfuric acid at a concentration of 60-70 wt%.

[0015] The specific operating steps are as follows: 1) Heat 60-70wt% sulfuric acid to 40-45℃, add ball-milled activated naphthalene tin phthalocyanine precursor to obtain slurry; 2) Heat the slurry to 48-55℃ and keep it at that temperature for 3-5 hours; 3) Dilute the slurry with deionized water until the sulfuric acid concentration is 40-50 wt%. 4) Heat the diluted slurry to 85-95℃ and keep it at that temperature for 0.5-2 hours; filter, wash with water until neutral, and dry to obtain the modified naphthalene phthalocyanine tin precursor.

[0016] The ball milling activation process effectively depolymerizes the microcrystalline clusters of tin phthalocyanine, reduces particle size, and improves component uniformity. Subsequent mild acid swelling treatment induces interlayer exfoliation and pore expansion, thereby constructing a precursor configuration with greater reactivity and mass transfer channels before pyrolysis. This pretreatment significantly improves the specific surface area of ​​the resulting SnO2 / carbon composite material by more than four times, enhancing interfacial contact quality and multi-scale pore structure.

[0017] (3) Preparation of tin oxide / nitrogen-doped carbon composite anode material derived from tin phthalocyanine: The modified phthalocyanine tin precursor obtained in step (2) was heat-treated in an inert atmosphere; after the heat treatment was completed, it was cooled down and oxidized by air to obtain the phthalocyanine tin derivative tin oxide / nitrogen-doped carbon composite anode material.

[0018] In this invention, the preparation method of the naphthyl phthalocyanine tin derivative tin oxide / nitrogen-doped carbon composite anode material, specifically the step (1) of preparing the naphthyl phthalocyanine tin precursor, is as follows: First, 2,3-dicyanonaphthalene and anhydrous stannous chloride are added to 1-chloronaphthalene to react and obtain a naphthalene-containing phthalocyanine tin intermediate; Then, the naphthalene-containing tin phthalocyanine intermediate was reduced with sodium borohydride; washed and dried to obtain the naphthalene-tin phthalocyanine precursor.

[0019] In this invention, the method for preparing the tin oxide / nitrogen-doped carbon composite anode material of the tin phthalocyanine derivative is as follows: in step (2), the grinding medium for S1 ball milling activation is selected as zirconium oxide beads or steel balls.

[0020] Preferably, the grinding media is zirconia beads.

[0021] In this invention, the preparation method of the naphthalene phthalocyanine tin derivative tin oxide / nitrogen-doped carbon composite negative electrode material, in step (2), S1 ball milling activation of the naphthalene phthalocyanine tin precursor: the mass ratio of the grinding media is 1:(10-40); the ball milling time is 12-16h.

[0022] Preferably, the mass ratio of the naphthalene phthalocyanine tin precursor to the grinding media is 1:30, and the ball milling time is 16 hours.

[0023] In this invention, the preparation method of the tin oxide / nitrogen-doped carbon composite anode material of the tin phthalocyanine derivative is wherein the mass ratio of sulfuric acid and ball-milled activated tin phthalocyanine precursor in step (2) of the S2 acid swelling treatment is (8-15):1.

[0024] In this invention, the preparation method of the naphthyl phthalocyanine tin derivative tin oxide / nitrogen-doped carbon composite anode material, the sulfuric acid concentration in step (2) of the S2 acid swelling treatment is 66wt%.

[0025] In this invention, the preparation method of the tin oxide / nitrogen-doped carbon composite anode material of the tin phthalocyanine derivative is as follows: in step (3), the heat treatment temperature is 500-700℃, the heat treatment time is 4-6h, and the heating rate is 3-8℃ / min; after the heat treatment is completed, the material is allowed to cool down naturally, and air is introduced to oxidize the material when the temperature drops to 300-400℃.

[0026] Preferably, the heat treatment temperature is 600℃, the heat treatment time is 5h, the heating rate is 5℃ / min, and the inert atmosphere is argon.

[0027] A tin oxide / nitrogen-doped carbon composite anode material of tin phthalocyanine derivative prepared by the above method has a BET specific surface area of ​​60-100 m². 2 / g, with pore sizes mainly distributed in the range of 2-10nm.

[0028] The material contains tin oxide and nitrogen-doped carbon; its XRD pattern shows characteristic diffraction peaks of tetragonal rutile SnO2; and its XPS pattern shows characteristic peaks of C, N, O, and Sn elements.

[0029] Application of a tin oxide / nitrogen-doped carbon composite anode material of tin phthalocyanine derivative prepared by the above preparation method in lithium-ion batteries.

[0030] The lithium-ion battery using the aforementioned tin oxide / nitrogen-doped carbon composite anode material with tin phthalocyanine derivative exhibits a discharge specific capacity of 650-800 mAh / g after 150 cycles at a current density of 0.1 A / g.

[0031] The beneficial effects of the present invention are as follows: The preparation method of the naphthalene phthalocyanine tin derivative tin oxide / nitrogen-doped carbon composite anode material of the present invention uses naphthalene phthalocyanine tin single-source precursor as tin source, carbon source and nitrogen source, without the need to introduce tin salt and external carbon source, and the process route is relatively simple.

[0032] More importantly, in the preparation of SnO2 / carbon composite materials, the naphthalene phthalocyanine tin single-source precursor is first pretreated. Modified naphthalene phthalocyanine tin precursor is obtained through ball milling activation and acid swelling synergistic pretreatment. This effectively dissociates the strong π–π stacking interaction between naphthalene phthalocyanine tin precursor molecules, significantly weakens its dense stacking structure, and at the same time completely preserves the chemical integrity and coordination stability of the naphthalene phthalocyanine macrocyclic skeleton.

[0033] After thermal conversion, the resulting composite anode material exhibits synergistic optimization in structural order, interfacial activity, and transport kinetics, displaying a more open hierarchical pore structure. This significantly enhances electrolyte wettability and accessibility to active sites, while also promoting electron / ion co-transport kinetics. The specific surface area increases by more than four times, and the mesopore volume and pore size distribution are significantly optimized, while the graphitization degree of the carbon matrix ( I D / I G The value remained basically unchanged, indicating that the carbon skeleton conductive network was not damaged.

[0034] When the composite material obtained by this invention is used as a negative electrode material for lithium-ion batteries, it exhibits good cycle performance, rate performance and low charge transfer impedance. Attached Figure Description

[0035] Figure 1 This is a process flow diagram of the preparation method of the tin oxide / nitrogen-doped carbon composite anode material of the tin phthalocyanine derivative.

[0036] Figure 2 The images show the XRD patterns of the naphthalene phthalocyanine tin precursor (SnNc) and the modified naphthalene phthalocyanine tin precursor described in this invention.

[0037] Figure 3 The images show the XRD patterns of SnNc-C obtained in Comparative Example 1 and the modified SnNc-C obtained in Example 1.

[0038] Figure 4 The images show the FT-IR spectra of SnNc and SnNc-C obtained in Comparative Example 1, and the modified SnNc and modified SnNc-C obtained in Example 1.

[0039] Figure 5 The nitrogen adsorption-desorption curves of SnNc-C obtained in Comparative Example 1 and the modified SnNc-C obtained in Example 1 were recorded at 77 K.

[0040] Figure 6 The images show the pore size distribution of SnNc-C obtained in Comparative Example 1 and the modified SnNc-C obtained in Example 1.

[0041] Figure 7 The image shows the XPS full spectrum of the modified SnNc-C obtained in Example 1.

[0042] Figure 8 This is a TEM image of the modified SnNc-C obtained in Example 1.

[0043] Figure 9 The graphs show the cycle performance of SnNc-C obtained in Comparative Example 1 and the modified SnNc-C obtained in Example 1 as negative electrode materials in lithium-ion batteries at 0.1 A / g.

[0044] Figure 10 The rate performance diagrams show the SnNc-C obtained in Comparative Example 1 and the modified SnNc-C obtained in Example 1 as negative electrode materials in lithium-ion batteries.

[0045] Figure 11 The AC impedance diagrams are shown for SnNc-C obtained in Comparative Example 1 and the modified SnNc-C obtained in Example 1, respectively, as negative electrode materials used in lithium-ion batteries.

[0046] Figure 12 The Raman spectra of SnNc-C obtained in Comparative Example 1 and the modified SnNc-C obtained in Example 1 are shown. Detailed Implementation

[0047] The technical solution of the present invention will be described in detail below.

[0048] All reagents were analytical grade and directly supplied by Shanghai Maclean's Biochemical Co., Ltd.

[0049] 1. X-ray diffraction (XRD) was performed using the German Bruker D8 ADVANCE.

[0050] 2. Fourier transform infrared spectroscopy (FTIR) was performed using a Thermo Nicolet IS50 from the USA.

[0051] 3. The scanning electron microscope (SEM) used was a German Zeiss MERLIN Compact.

[0052] 4. The transmission electron microscope (TEM) used was a FEI Tecnai G2 F20 from the USA.

[0053] 5. X-ray photoelectron spectroscopy (XPS) was performed using a Thermo ESCALAB 250 from the USA.

[0054] 6. Specific surface area and pore size distribution were determined using the Brunauer-Emmett-Teller (BET) method and the Barrett-Joyner-Halenda model, respectively.

[0055] 7. Raman spectroscopy was performed using B&W Tek Corporation, USA.

[0056] 8. Electrode preparation: The working electrode is prepared by homogenizing an active material (SnNc-C or modified SnNc-C), Super P conductive carbon and polyvinylidene fluoride (PVDF) in an N-methyl-2-pyrrolidone (NMP) solvent at a weight ratio of 7:2:1.

[0057] The slurry was uniformly coated onto the copper foil current collector and dried under vacuum at 100°C for 12 hours.

[0058] Subsequently, the electrode was pressed into a circular sheet with a diameter of 12 mm, and the areal mass loading was controlled to be 0.7-0.8 mg / cm². 2 .

[0059] The CR2032 button cell is assembled in an argon-filled glove box (H2O, O2 < 0.1ppm), using lithium foil as the counter electrode and Celgard2500 (PP) as the separator.

[0060] The electrolyte is prepared by dissolving 1.0 M LiPF6 in a ternary mixture of ethylene dicarbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) in a volume ratio of 1:1:1.

[0061] 9. Electrochemical Measurement: At room temperature, using the LAND CT 3002 test system, with a test voltage of 0.01-3.0V (vs. Li / Li), + Constant current charge-discharge (GCD) and constant current intermittent titration (GITT) tests were performed within the specified range.

[0062] Prior to GITT measurements, the electrodes were subjected to several constant current charge-discharge cycles to obtain a stable electrochemical state.

[0063] GITT measurement at a specific current of 0.1 A·g -1 The current is normalized according to the mass of the active material.

[0064] Cyclic voltammetry (CV) was performed using an electrochemical workstation (CHI760E, Shanghai) at a range of 0.1 to 2.0 mV·s. -1 It was performed at different scan rates.

[0065] Electrochemical impedance spectroscopy (EIS) was recorded in the frequency range of 100 kHz to 0.01 Hz with a sinusoidal perturbation amplitude of 10 mV.

[0066] Example 1 The specific steps for preparing the naphthylphthalocyanine tin derivative tin oxide / nitrogen-doped carbon composite anode material are as follows: (1) Preparation of naphthalene phthalocyanine tin precursor; First, 2.85 g of 2,3-dicyanonaphthalene and 1.77 g of anhydrous stannous chloride were added to 25 mL of 1-chloronaphthalene, stirred and heated, reacted at 180 °C for 1 h, then at 210 °C for 1 h, and then refluxed for 2 h.

[0067] After the reaction was complete, the precipitate was collected by filtration, washed successively with methanol, pyridine and methanol, and dried under vacuum to obtain the tin phthalocyanine intermediate (SnNcCl2).

[0068] Then, 2.05 g of the obtained naphthyl phthalocyanine tin intermediate (SnNcCl2) and 0.741 g of sodium borohydride (NaBH4) were added to 20 mL of pyridine and refluxed for 1 h.

[0069] After the reaction solution cools, add 15 mL of deionized water and continue reflux for 30 min to obtain a reaction suspension.

[0070] Finally, the reaction suspension was poured into ice water, filtered to collect the filter cake, washed with methanol and deionized water, and dried to obtain the naphthalene tin phthalocyanine precursor, denoted as SnNc.

[0071] (2) Preparation of modified naphthalene phthalocyanine tin precursor: S1. Ball milling activation: Take 0.5g of SnNc obtained in step (1), add 15g of zirconia beads, and ball mill at 110℃ for 16h to obtain ball-milled SnNc.

[0072] S2, Acid Swelling Treatment: 1) Heat 7.2g of 66wt% sulfuric acid to 43℃, add ball-milled activated SnNc to obtain a slurry; 2) Heat the slurry to 50℃ and keep it at that temperature for 4 hours; 3) Dilute the slurry with deionized water until the sulfuric acid concentration is 45 wt%. 4) Heat the diluted slurry to 90℃ and keep it at that temperature for 1 hour; filter, wash with water until neutral, and dry to obtain the modified naphthalene tin phthalocyanine precursor, denoted as modified SnNc.

[0073] (3) Preparation of tin oxide / nitrogen-doped carbon composite anode material derived from tin phthalocyanine: The modified SnNc obtained in step (2) was placed in a ceramic boat and heated to 600°C at a heating rate of 5°C / min under an argon atmosphere, and held for 5 hours.

[0074] After the heat preservation is completed, the material is allowed to cool down naturally. When the temperature drops to 350℃, air is introduced for oxidation. After the oxidation is completed, the material is cooled to room temperature to obtain a tin oxide / nitrogen-doped carbon composite anode material derived from tin phthalocyanine, denoted as modified SnNc-C.

[0075] When the modified SnNc-C obtained in Example 1 is used as an anode material in lithium-ion batteries, at 1.0 A·g - ¹After 500 stable cycles at high rates, it still maintains a capacity of 399.8 mAh·g. -1 The capacity.

[0076] pass Figure 2 The XRD pattern shows that SnNc has obvious diffraction peaks, indicating that it has a certain degree of ordered packing. The diffraction peaks of the modified SnNc obtained after pretreatment are broadened and weakened, indicating that ball milling activation and acid swelling treatment can change the packing state of the naphthalene phthalocyanine tin precursor SnNc.

[0077] pass Figure 3 The XRD pattern shows that the modified SnNc-C exhibits characteristic SnO2 diffraction peaks, indicating that tin oxide species are formed after heat treatment and air oxidation.

[0078] pass Figure 4 It can be seen that the modified SnNc retains the relevant characteristic peaks of naphthalene phthalocyanine tin without significant shift, indicating that the conjugated macrocycle remains intact after ball milling activation and acid expansion.

[0079] During calcination, the skeletal features in SnNc-C and modified SnNc-C persisted, indicating that the carbonization process retained the residual macrocyclic units rather than transforming them into featureless amorphous nitrogen-doped carbon. This structural retention is crucial for maintaining active coordination sites in carbon-based composites, providing additional active sites for lithium-ion storage and contributing to improved electrochemical performance.

[0080] By Figure 5 and Figure 6 It can be seen that the BET specific surface area of ​​the modified SnNc-C obtained in Example 1 is 84.60 m². 2 / g, higher than the 20.21m of SnNc-C obtained in Comparative Example 1. 2 / g. Furthermore, the pore size of the modified SnNc-C obtained in Example 1 is mainly distributed in the range of 2-10 nm. The increased specific surface area and abundant mesoporous channels facilitate electrolyte permeation and shorten the effective Li₂ period. + This facilitates transport pathways and provides more electrolyte-accessible areas for electrochemical reactions.

[0081] pass Figure 7 The XPS full spectrum shows that the modified SnNc-C contains C, N, O and Sn elements.

[0082] pass Figure 8 As can be seen, the modified SnNc-C obtained in Example 1 has a porous granular structure. The secondary particles of the modified SnNc-C consist of ultrafine primary nanocrystals with grain boundary voids, forming an internally porous aggregated structure. This morphology indicates the presence of accessible SnO2 / carbon regions within the secondary particles, rather than a simple size-controlled feature. It is evident that after pretreatment and calcination, the modified SnNc-C exhibits dense secondary aggregates while retaining a large number of internal pores and maintaining nanoscale crystalline SnO2 regions.

[0083] pass Figures 9-11 The test results show that when the modified SnNc-C obtained in Example 1 is used as a negative electrode material in lithium-ion batteries, it exhibits good performance at 0.1 A·g -1 It still maintains 741.2 mAh·g after 150 cycles at the current density. -1 The reversible specific capacity, compared to the untreated SnNc-C control sample obtained in Comparative Example 1 (542.7 mAh g⁻¹), was significantly higher. - ¹) An increase of 36.6%.

[0084] After the initial activation / stabilization phase, the coulombic efficiency approached 100% under both conditions, indicating that the electrode / electrolyte interface remained stable during long-term cycling. This demonstrates that the material exhibits good rate performance and long-term cycling stability, further confirming the structural advantages of modified SnNc-C in achieving long-term lithium-ion storage at high current densities.

[0085] Further EIS testing was conducted to evaluate the interfacial kinetics of SnNc-C and modified SnNc-C. The charge transfer impedance (Rct) of the modified SnNc-C in Example 1 was 186.0 Ω, lower than the 259.7 Ω of the SnNc-C obtained in Comparative Example 1. This indicates that the modified SnNc-C prepared by the method described in this invention exhibits superior interfacial charge transfer kinetics and lower electrode polarization.

[0086] pass Figure 12 It can be seen that the modified SnNc-C obtained in Example 1 has... I D / I G The ratio was 0.93, while the untreated SnNc-C obtained in Comparative Example 1... I D / I GThe ratio of 0.92 indicates that although ball milling-assisted acid expansion significantly altered the crystal structure of the precursor, the carbon matrices obtained from both samples after heat treatment exhibited similar degrees of graphitization and defect densities. Therefore, the pretreatment did not significantly change the ordered structure of the carbon formed during carbonization.

[0087] The modified SnNc-C obtained in this embodiment was used as the negative electrode material in a lithium-ion battery, and the rate performance and long-cycle performance of the battery were tested. The test results are detailed in Table 1.

[0088] Table 1 Rate performance and long-cycle performance of modified SnNc-C

[0089] As shown in Table 1, the modified SnNc-C exhibits high discharge specific capacity at different current densities, and maintains high capacity even after long cycling at 0.8 A / g and 1.0 A / g, indicating that it can continuously store charge at high current densities and maintain an effective ion / electron transport channel.

[0090] Furthermore, in the SnNc-C obtained in Comparative Example 1, Li... + The diffusion coefficient is 3.04 × 10⁻⁶. -9 ~2.77×10 -8 cm 2 ·s -1 During charging, the value is 2.10 × 10. -9 ~5.91×10 -8 cm 2 ·s -1 .

[0091] In contrast, the modified SnNc-C obtained in Example 1 exhibited higher LiN values ​​over most of the test voltage range. + The diffusion coefficient reaches 8.02 × 10⁻⁶ during discharge. -9 ~4.36×10 -8 cm 2 ·s -1 The charge value is 3.43 × 10⁻⁶. -9 ~1.47×10 - 7 cm 2 ·s -1 This indicates its effective Li-carbide content during the lithiation / delithiation process. + It offers superior transmission performance.

[0092] Comparative Example 1 The difference between this comparative example and Example 1 is that SnNc is not subjected to ball milling activation and acid swelling treatment, but is directly processed to obtain SnNc-C.

[0093] The specific steps are as follows: (1) Preparation of naphthalene phthalocyanine tin precursor; First, 2.85 g of 2,3-dicyanonaphthalene and 1.77 g of anhydrous stannous chloride were added to 25 mL of 1-chloronaphthalene, stirred and heated, reacted at 180 °C for 1 h, then at 210 °C for 1 h, and then refluxed for 2 h.

[0094] After the reaction was complete, the precipitate was collected by filtration, washed successively with methanol, pyridine and methanol, and dried under vacuum to obtain the tin phthalocyanine intermediate (SnNcCl2).

[0095] Then, 2.05 g of the obtained naphthyl phthalocyanine tin intermediate (SnNcCl2) and 0.741 g of sodium borohydride (NaBH4) were added to 20 mL of pyridine and refluxed for 1 h.

[0096] After the reaction solution cools, add 15 mL of deionized water and continue reflux for 30 min to obtain a reaction suspension.

[0097] Finally, the reaction suspension was poured into ice water, filtered to collect the filter cake, washed with methanol and deionized water, and dried to obtain the naphthalene tin phthalocyanine precursor, denoted as SnNc.

[0098] (2) Preparation of SnNc-C composite anode material: The SnNc obtained in step (1) was placed in a ceramic boat and heated to 600°C at a heating rate of 5°C / min under an argon atmosphere, and held at that temperature for 5 hours.

[0099] After the heat preservation is completed, the material is allowed to cool down naturally. When the temperature drops to 350℃, air is introduced for oxidation. After the oxidation is completed, the material is cooled to room temperature to obtain the composite anode material, denoted as SnNc-C.

[0100] Comparative Example 2 The difference between this comparative example and Example 1 is that SnNc is only activated by ball milling without acid swelling treatment to obtain ball-milled SnNc-C.

[0101] The specific steps are as follows: (1) Preparation of naphthalene phthalocyanine tin precursor; First, 2.85 g of 2,3-dicyanonaphthalene and 1.77 g of anhydrous stannous chloride were added to 25 mL of 1-chloronaphthalene, stirred and heated, reacted at 180 °C for 1 h, then at 210 °C for 1 h, and then refluxed for 2 h.

[0102] After the reaction was complete, the precipitate was collected by filtration, washed successively with methanol, pyridine and methanol, and dried under vacuum to obtain the tin phthalocyanine intermediate (SnNcCl2).

[0103] Then, 2.05 g of the obtained naphthyl phthalocyanine tin intermediate (SnNcCl2) and 0.741 g of sodium borohydride (NaBH4) were added to 20 mL of pyridine and refluxed for 1 h.

[0104] After the reaction solution cools, add 15 mL of deionized water and continue reflux for 30 min to obtain a reaction suspension.

[0105] Finally, the reaction suspension was poured into ice water, filtered to collect the filter cake, washed with methanol and deionized water, and dried to obtain the naphthalene tin phthalocyanine precursor, denoted as SnNc.

[0106] (2) Preparation of ball-milled SnNc: Take 0.5g of SnNc obtained in step (1), add 15g of zirconia beads, and ball mill at 110℃ for 16h to activate it; to obtain ball-milled SnNc.

[0107] (3) Preparation of ball-milled SnNc-C: The ball-milled SnNc obtained in step (2) was placed in a ceramic boat and heated to 600°C at a heating rate of 5°C / min under an argon atmosphere, and held at that temperature for 5 hours.

[0108] After the heat preservation is completed, the temperature is allowed to drop naturally. When the temperature drops to 350℃, air is introduced for oxidation. After the oxidation is completed, the mixture is cooled to room temperature to obtain ball-milled SnNc-C.

[0109] Comparative Example 3 The difference between this comparative example and Example 1 is that SnNc is only subjected to acid swelling treatment without ball milling activation to obtain acid-swelled SnNc-C.

[0110] The specific steps are as follows: (1) Preparation of naphthalene phthalocyanine tin precursor; First, 2.85 g of 2,3-dicyanonaphthalene and 1.77 g of anhydrous stannous chloride were added to 25 mL of 1-chloronaphthalene, stirred and heated, reacted at 180 °C for 1 h, then at 210 °C for 1 h, and then refluxed for 2 h.

[0111] After the reaction was complete, the precipitate was collected by filtration, washed successively with methanol, pyridine and methanol, and dried under vacuum to obtain the tin phthalocyanine intermediate (SnNcCl2).

[0112] Then, 2.05 g of the obtained naphthyl phthalocyanine tin intermediate (SnNcCl2) and 0.741 g of sodium borohydride (NaBH4) were added to 20 mL of pyridine and refluxed for 1 h.

[0113] After the reaction solution cools, add 15 mL of deionized water and continue reflux for 30 min to obtain a reaction suspension.

[0114] Finally, the reaction suspension was poured into ice water, filtered to collect the filter cake, washed with methanol and deionized water, and dried to obtain the naphthalene tin phthalocyanine precursor, denoted as SnNc.

[0115] (2) Preparation of acid-expanded SnNc: 1) Heat 7.2g of 66wt% sulfuric acid to 43℃ and add SnNc obtained in step (1) to obtain slurry; 2) Heat the slurry to 50℃ and keep it at that temperature for 4 hours; 3) Dilute the slurry with deionized water until the sulfuric acid concentration is 45 wt%. 4) Heat the diluted slurry to 90℃ and keep it at that temperature for 1 hour; filter, wash with water until neutral, and dry to obtain the modified naphthalene tin phthalocyanine precursor, denoted as acid-swelling SnNc.

[0116] (3) Preparation of acid-expanded SnNc-C: The acid-expanded SnNc obtained in step (2) was placed in a porcelain boat and heated to 600°C at a heating rate of 5°C / min under an argon atmosphere, and held at that temperature for 5 hours.

[0117] After the heat preservation is completed, the temperature is allowed to drop naturally. When the temperature drops to 350℃, air is introduced for oxidation. After the oxidation is completed, the mixture is cooled to room temperature to obtain acid-expanded SnNc-C.

[0118] Comparative Example 4 The difference between this comparative example and Example 1 is that the S1 ball milling activation temperature in step (2) of preparing the modified naphthalene phthalocyanine tin precursor is 25°C.

[0119] The other examples are the same as in Example 1, resulting in the composite anode material of Comparative Example 4.

[0120] Comparative Example 5 The difference between this comparative example and Example 1 is that the dilution step was not performed in the S2 acid swelling treatment operation in step (2) of preparing the modified naphthalene phthalocyanine tin precursor.

[0121] Specifically as follows: S2, Acid Swelling Treatment: 1) Heat 7.2g of 66wt% sulfuric acid to 43℃, add ball-milled activated SnNc to obtain a slurry; 2) Heat the slurry to 50℃ and keep it at that temperature for 4 hours; 3) Heat the slurry to 90℃ and keep it at that temperature for 1 hour; filter, wash with water until neutral, and dry.

[0122] The other steps were the same as in Example 1, resulting in the composite anode material of Comparative Example 5.

[0123] The composite anode materials obtained in Example 1 and Comparative Example 1 were subjected to structural characterization tests and electrochemical performance tests. The test results are detailed in Table 2.

[0124] Table 2 Structural and electrochemical performance indicators

[0125] As shown in Table 2, the modified SnNc-C obtained in Example 1 has a higher BET specific surface area and a higher post-cycle discharge specific capacity than the SnNc-C obtained in Comparative Example 1, and a lower charge transfer impedance than SnNc-C. This indicates that the synergistic pretreatment in the preparation method of the present invention can improve the cycle stability of the naphthalene phthalocyanine tin-derived anode material and reduce the interface impedance.

[0126] To illustrate the necessity of combining ball milling activation and acid swelling treatment, electrochemical tests were performed on the materials obtained in Example 1, Comparative Example 2, and Comparative Example 3. The test results are shown in Table 3.

[0127] Table 3 Comparison of electrochemical performance of materials obtained from different pretreatment routes

[0128] As shown in Table 3, the electrochemical performance of the materials obtained in Comparative Examples 2 and 3 is generally lower than that of the modified SnNc-C obtained in Example 1, indicating that neither ball milling activation nor acid swelling treatment alone can achieve the effect of Example 1. The combined use of ball milling activation and acid swelling treatment described in this invention is more beneficial to improving the electrochemical performance of the obtained composite anode material.

[0129] To illustrate the effects of ball milling activation temperature and acid swelling dilution steps, cyclic tests were conducted on the materials obtained in Example 1, Comparative Example 4, and Comparative Example 5. The results are shown in Table 4.

[0130] Table 4 Comparison of Cyclic Performance of Materials Obtained Under Different Processing Conditions

[0131] As shown in Table 4, the discharge specific capacity of Comparative Example 4 and Comparative Example 5 after 50 cycles is lower than that of Example 1, indicating that the ball milling activation temperature and acid swelling dilution steps described in Example 1 are beneficial to improving the material's cycle performance.

Claims

1. A method for preparing a tin oxide / nitrogen-doped carbon composite anode material derived from naphthalene phthalocyanine, characterized in that, Includes the following steps: (1) Preparation of naphthalene phthalocyanine tin precursor; The naphthalene phthalocyanine tin precursor was prepared using 2,3-dicyanonaphthalene and anhydrous stannous chloride as raw materials. (2) Preparation of modified naphthalene phthalocyanine tin precursor: The naphthalene phthalocyanine tin precursor prepared in step (1) was subjected to ball milling activation and acid swelling treatment in sequence to obtain the modified naphthalene phthalocyanine tin precursor; S1. Ball milling activation: A grinding medium was added to the naphthalene phthalocyanine tin precursor prepared in step (1), and ball milling activation was performed at 105-110℃; S2, Acid Swelling Treatment: The ball-milled activated naphthalene tin phthalocyanine precursor was subjected to acid swelling treatment with sulfuric acid at a concentration of 60-70 wt%. The specific steps for acid swelling treatment are as follows: 1) Heat 60-70wt% sulfuric acid to 40-45℃, add ball-milled activated naphthalene tin phthalocyanine precursor to obtain slurry; 2) Heat the slurry to 48-55℃ and keep it at that temperature for 3-5 hours; 3) Dilute the slurry with deionized water until the sulfuric acid concentration is 40-50 wt%. 4) Heat the diluted slurry to 85-95℃ and keep it at that temperature for 0.5-2 hours; filter, wash with water until neutral, and dry to obtain the modified naphthalene tin phthalocyanine precursor; (3) Preparation of tin oxide / nitrogen-doped carbon composite anode material derived from tin phthalocyanine: The modified phthalocyanine tin precursor obtained in step (2) was heat-treated in an inert atmosphere; after the heat treatment was completed, it was cooled down and oxidized by air to obtain the phthalocyanine tin derivative tin oxide / nitrogen-doped carbon composite anode material.

2. The preparation method of the tin oxide / nitrogen-doped carbon composite anode material of tin phthalocyanine derivative according to claim 1, characterized in that, The specific steps for preparing the naphthyl phthalocyanine tin precursor in step (1) are as follows: First, 2,3-dicyanonaphthalene and anhydrous stannous chloride are added to 1-chloronaphthalene to react and obtain a naphthalene-containing phthalocyanine tin intermediate; Then, the naphthalene-containing tin phthalocyanine intermediate was reduced with sodium borohydride; Wash and dry to obtain the naphthalene phthalocyanine tin precursor.

3. The method for preparing the tin oxide / nitrogen-doped carbon composite anode material of tin phthalocyanine derivative according to claim 1, characterized in that, The grinding media for S1 ball milling activation in step (2) are selected as zirconia beads or steel balls; Preferably, the grinding media is zirconia beads.

4. The method for preparing the tin oxide / nitrogen-doped carbon composite anode material of tin phthalocyanine derivative according to claim 1, characterized in that, In step (2), the S1 ball milling activation of the naphthalene phthalocyanine tin precursor is performed with a grinding media mass ratio of 1:(10-40) and a ball milling time of 12-16 hours. Preferably, the mass ratio of the naphthalene phthalocyanine tin precursor to the grinding media is 1:30, and the ball milling time is 16 hours.

5. The method for preparing the tin oxide / nitrogen-doped carbon composite anode material of tin phthalocyanine derivative according to claim 1, characterized in that, The mass ratio of sulfuric acid and ball-milled activated naphthalene tin phthalocyanine precursor in step (2) for the S2 acid swelling treatment is (8-15):

1.

6. The method for preparing the tin oxide / nitrogen-doped carbon composite anode material of tin phthalocyanine derivative according to claim 1, characterized in that, The sulfuric acid concentration in the S2 acid swelling treatment in step (2) is 66 wt%.

7. The method for preparing the tin oxide / nitrogen-doped carbon composite anode material of tin phthalocyanine derivative according to claim 1, characterized in that, The heat treatment temperature in step (3) is 500-700℃, the heat treatment time is 4-6h, and the heating rate is 3-8℃ / min. After the heat treatment is completed, the temperature is allowed to drop naturally, and air is introduced to oxidize when the temperature drops to 300-400℃.

8. The method for preparing the tin oxide / nitrogen-doped carbon composite anode material of tin phthalocyanine derivative according to claim 7, characterized in that, The heat treatment temperature in step (3) is 600℃, the heat treatment time is 5h, the heating rate is 5℃ / min, and the inert atmosphere is argon.

9. A tin oxide / nitrogen-doped carbon composite anode material of tin phthalocyanine derivative prepared by any one of the preparation methods described in 1-8, characterized in that, The BET specific surface area of ​​this composite anode material is 60-100 m². 2 / g, with pore sizes mainly distributed in the range of 2-10nm.

10. The application of a tin oxide / nitrogen-doped carbon composite anode material of tin phthalocyanine derivative prepared by any one of the preparation methods described in 1-8 in lithium-ion batteries, characterized in that, The lithium-ion battery using the aforementioned tin oxide / nitrogen-doped carbon composite anode material with tin phthalocyanine derivative exhibits a discharge specific capacity of 650-800 mAh / g after 150 cycles at a current density of 0.1 A / g.